Comparative response of Indian mustard (Brassica juncea) to sulphur sources on vertisols of Rajasthan - Meena, Bhawani Shankar; Meena, D. S. (Annals of Agricultural Research, 2016)
A field experiment was conducted on clay loam soil in rabi seasons of 2011-12 and 2012 -13 at farmer’s field with 5 nutrient management practices viz., RDF(80 kg N and 40 kg P2O5/ha) + 40 kg S/ha through elemental sulphur at 2 week before sowing , RDF + 40 kg S/ ha through bentonite sulphur at sowing, RDF + 40 kg S/ha through gypsum at 2 week before sowing, RDF + 12 kg S/ha through bentonite sulphur at sowing, and RDF+ without sulphur to find out requirement and best source of sulphur for Indian mustard grown on vertisols under irrigated condition. Application of 40 kg S/ha through bentonite sulphur along with RDF recorded significantly higher plant height (191.0 cm), dry matter/plant (55.8 g), secondary branches/plant (14.6), siliqua/plant (336.3), seeds/siliqua (16.8), 1000 -seed weight (6.0 g), seed yield (2.45 t/ha), net return (` 59,200/ha) and benefit: cost ratio (3 :1), oil content (37.8 %) and oil yield (926 kg/ha) over RDF + without sulphur application and RDF + 12 kg S/ha by bentonite sulphur and RDF + 40 kg S/ha by gypsum applied at 2 weeks before sowing and was at par with RDF + 40 kg S/ha by elemental sulphur. Application of 40 kg S/ha through bentonite sulphur at sowing with RDF recorded significantly higher N (100.2 kg/ha), P (28.0 kg/ha) and S (16.8 kg/ha) uptake by crop and available nitrogen (298.2 kg/ha), phosphorus (11.5 kg/ha) and sulphur (17.5 kg/ha) contents in the soil over rest of the treatments. Agronomic efficiency and apparent recovery of N, P and S were higher with application of 40 kg S/ha through bentonite sulphur along with RDF as compared to other treatments. Production (17.75 kg/ha/day) and economics efficiency (`429/ha/day) significantly recorded higher in treatment RDF +40 kg S/ha through bentonite sulphur over RDF+ without sulphur , farmer practices and was at par with RDF + 40 kg S/ha by elemental sulphur and RDF + 40 kg S/ha by gypsum.